Analysing chemical attraction of gravid Anopheles gambiae sensu stricto with modified BG-Sentinel traps - Okal, Michael N. (Parasit Vectors, 2015)
BACKGROUND: Cues that guide gravid Anopheles gambiae sensu lato to oviposition sites can be manipulated to create new strategies for monitoring and controlling malaria vectors. However, progress towards identifying such cues is slow in part due to the lack of appropriate tools for investigating long-range attraction to putative oviposition substrates. This study aimed to develop a relatively easy-to-use bioassay system that can effectively analyse chemical attraction of gravid Anopheles gambiae sensu stricto. METHODS: BG-Sentinel™ mosquito traps that use fans to dispense odourants were modified to contain aqueous substrates. Choice tests with two identical traps set in an 80 m(2) screened semi-field system were used to analyse the catch efficacy of the traps and the effectiveness of the bioassay. A different batch of 200 gravid An. gambiae s.s. was released on every experimental night. Choices tested were (1) distilled versus distilled water (baseline) and (2) distilled water versus soil infusion. Further, comparisons were made of distilled water and soil infusions both containing 150 g/l of Sodium Chloride (NaCl). Sodium Chloride is known to affect the release rate of volatiles from organic substrates. RESULTS: When both traps contained distilled water, 45 % (95 confidence interval (CI) 33–57 %) of all released mosquitoes were trapped. The proportion increased to 84 % (95 CI 73–91 %) when traps contained soil infusions. In choice tests, a gravid female was twice as likely to be trapped in the test trap with soil infusion as in the trap with distilled water (odds ratio (OR) 1.8, 95 % CI 1.3–2.6). Furthermore, the attraction of gravid females towards the test trap with infusion more than tripled (OR 3.4, 95 % CI 2.4–4.8) when salt was added to the substrates. CONCLUSION: Minor modifications of the BG-Sentinel™ mosquito trap turned it into a powerful bioassay tool for evaluating the orientation of gravid mosquitoes to putative oviposition substrates using olfaction. This study describes a useful tool for investigating olfactory attraction of gravid An. gambiae s.s. and provides additional evidence that gravid mosquitoes of this species are attracted to and can be baited with attractive substrates such as organic infusions over a distance of several metres.